Kepercayaan Masyarakat Terhadap Benda Yang Dikeramatkan di Pulau Subi Kecamatan Subi Kabupaten Natuna - Ciciana; Nanik Rahmawati; Marisa Elsera (CV Insan Kreasi Media, 2023)
The people of Subi Island, Natuna Regency still have confidence in objects that are sacred by themselves. Almost all of the people of Subi Island still have faith in sacred objects, although at this time the people's way of thinking has begun to open, but on the one hand, the way of thinking that has been opened earlier, they still strongly believe in the supernatural in things. Therefore, the researcher raised the title of public trust in sacred objects with the formulation of the problem of how the public views the phenomenon. The research method used in this study is a qualitative method with a descriptive approach. The informant determination technique used is purposive sampling with the criteria of informants, namely traditional leaders, village heads, people who have lived permanently on the island of Subi for 40 years, people who have not received education, people who are graduates, people who know stories about sacred objects, and the number of people who know about sacred objects. 8 informants. The data collection techniques used are observation, interviews, documentation with data sources, secondary data and primary data. With data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results of his research are that there are 4 public trusts in sacred objects, the sacred tok lile, the sacred blood of putig tomb, the sea, and the huntan. The reason people believe in these sacred objects is because the first one is entrusted to them by their ancestors/ancestors. Trust from ancestors/ancestors that are recognized and obligatory for the community to believe in it. Where the Malay people are still thick with existing customs and then are still steadfast and obedient to their ancestor's deposit. Second, the parent's deposit. Parents play an important role in the child's growth process. As a Malay, the people of Pulau Subi feel that something is missing when they cannot follow or carry out the advice of their parents. Third, it has existed for a long time so it is difficult to get rid of it. Belief in sacred objects is preserved by the community so that it has become a habit in their lives. This belief has become part of their culture and is difficult to let go of.